Fellner on Competition Among the Few - Rothschild, K. W. (Quarterly Journal of Economics, 1952)
Journal Article Fellner on Competition Among the Few Get access K. W. Rothschild K. W. Rothschild Österreichisches Institut für Wirtschaftsforschung, Vienna Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 66, Issue 1, February 1952, Pages 128–136, https://doi.org/10.2307/1882082 Published: 01 February 1952